Construction and validation of a novel ferroptosis-related signature for evaluating prognosis and immune microenvironment in ovarian cancer - Yang, Jiani; Wang, Chao; Cheng, Shanshan; Zhang, Yue; Jin, Yue; Zhang, Nan; Wang, Yu (Frontiers in Genetics, 2023)
Ovarian cancer (OV) is the most lethal form of gynecological malignancies worldwide, with limited therapeutic options and high recurrence rates. However, research focusing on prognostic patterns of ferroptosis-related genes (FRGs) in OV is still lacking. From the 6406 differentially expressed genes (DEGs) between TCGA-OV (n=376) and GTEx cohort (n=180), we identified 63 potential FRGs. Through the LASSO-penalized Cox analysis, 3 prognostic genes, SLC7A11, ZFP36, and TTBK2, were finally distinguished. The time-dependent ROC curves and K-M survival analysis performed powerful prognostic ability of the 3-gene signature. Stepwise, we constructed and validated the nomogram based on the 3-gene signature and clinical features, with promising prognostic value in both TCGA (P-value<0.0001) and ICGC cohort (P-value=0.0064). Gene Set Enrichment Analysis elucidated several potential pathways between the groups stratified by 3-gene signature, while the m6A gene analysis implied higher m6A level in the high-risk group. We applied the CIBERSORT algorithm to distinct tumor immune microenvironment between two groups, with less activated DCs and plasma cells, more M0 macrophages infiltration, and higher expression of key immune checkpoint molecules (CD274, CTLA4, HAVCR2, and PDCD1LG2) in the high-risk group. In addition, the low-risk group exhibited more favorable immunotherapy and chemotherapy responses. Collectively, our findings provided new prospects in the role of FRGs, as a promising prediction tool for prognosis and immune responses, in order to assist personalized treatment decision-making among OV patients.